Medical Disorders in Pregnancy Among Inpatients at a Tertiary Level Hospital of Peshawar (Khyber Pakhtunkhwa) - Rubina Akhtar; Rukhsana Karim; Nasreen Kishwar; Saba Safdar (Gandhara University, 2024)
OBJECTIVES This study aimed to determine the prevalence, type, and demographic makeup of pregnancy-related medical conditions among patients receiving treatment in a tertiary care facility. METHODOLOGY The Monocentric retrospective impact study was conducted in the Department of Obstetrics and Gynaecology of MTI, Hayatabad Medical Complex Peshawar, from January to December 2022. Case records of all pregnant women (n=1811) with previous or recently developed medical conditions treated during the study period were collected from the records / medical registers, and all the information was recorded in a pre-structured proforma. All women with previous or recently developed medical conditions treated during the study were included. All pregnant women without any medical conditions were excluded. Data was analyzed using simple statistical measures, and the results were presented as frequency percentages. Prior approval from the institution's ethical committee was obtained to conduct the study. vRESULTS Among 6327 antenatal admissions, 1811 (28.62%) women had medical disorders. The most common medical disorder was PIH, reported in 384 (21.20%) of the females, followed by RH incompatibility and Gestational Diabetes Mellitus (GDM) seen in 235 (12.98%) and 205 (11.32%) females, respectively. Other notable medical conditions include UTI in 170 (9.39%), Chronic HTN in 134 (7.40%), iron deficiency anemia in 122 (6.74%), and pre-eclampsia in 100 (5.52%) of women. CONCLUSION Pre-existing medical conditions in pregnancy are not uncommon. Early recognition of acute illness and treatment of chronic conditions in pregnancy is of clear benefit and needs to be managed to arrest any adversaries to the mother and fetus.